Psychological responses to recorded music as predictors of intentions to attend concerts: Emotions, liking, performance evaluations, and monetary value. (June 2016) - Kawase, Satoshi; Obata, Satoshi
The present study was designed to investigate how music listening affects intentions to attend concerts by employing both the music consumption model and the general consumer behavior model in service environments. We conducted a listening experiment using live recorded classical music. Participants responded to questionnaires after listening to pieces that represented different types of emotions. The items surveyed included felt emotion, liking, performance evaluation, and monetary value. The main findings were as follows: (1) strong emotions that were linked with happiness and tenderness/liking induced by music listening and performance evaluations were associated with intentions to attend concerts, and (2) the individual sense of the value of classical music also influenced the price that audience members were willing to pay to attend a concert when inspired to do so through music listening.